Verbal deficits in Down's syndrome and specific language impairment: a comparison. - Laws, G; Bishop, D (2004)
BACKGROUND: Down's syndrome is a chromosome disorder characterized by a range of physical and psychological conditions, including language impairment. The severity of impairment is variable, and some components of the language system appear to be more affected than others. This description could also be applied to typically developing children diagnosed with specific language impairment. AIMS: To compare findings from the largely separate research literatures on these conditions, and to address the questions about whether the language pathology associated with Down's syndrome could be the same as that described as specific language impairment in typical development, and whether the two conditions could have similar causes. MAIN CONTRIBUTION: Research studies suggest similar patterns of language impairment in the two populations, and some similarities in underlying processing deficits. CONCLUSIONS: Future research should consider whether similarities in the language behaviours associated with Down's syndrome and specific language impairment could be related to similarities at other levels of analysis, including neurological development and genetics.